FDG PET-CT in Clinical Management of a Rare Case of Primary Hepatic Lymphoma: Role and Challenges - Jain, Tarun Kumar; Gupta, Naveen; Malhotra, Hemant; Sharma, Lalit Mohan (World journal of nuclear medicine, 2023)
The common differential diagnoses for multiple space-occupying hepatic lesions (SOL) are metastases, multifocal hepatocellular carcinoma, and abscess. Primary hepatic lymphomas are rare entities that present many challenges with regard to their management. Fluorodeoxyglucose positron emission tomography-computed tomography is extensively used for the staging and response assessment of lymphomas but it can be challenging and difficult to interpret in cases with isolated liver involvement. We hereby present the case of an 82-year-old lady who presented with multiple liver SOL.